Crawler Crane Productivity Analysis on Erection Girder Work for Toll Road Construction Solo - Yogyakarta - Astuti Umasugi; Sely Novita Sari; Rizal Maulana (G-Tech: Jurnal Teknologi Terapan, 2025)
The construction of the Solo–Yogyakarta Toll Road aims to enhance connectivity between Solo and Yogyakarta and reduce traffic congestion. This study examines the productivity of crawler cranes in girder erection work to provide recommendations for optimizing crane usage in similar projects and improving construction efficiency. A quantitative approach was used, analyzing technical parameters such as lifting capacity, load charts, and operational safety, in accordance with SNI 6910-2022 standards. The findings revealed that the IHI CCH2800 crawler crane, with a maximum capacity of 280 tons, successfully handled a total load of 44.61 tons using a lifting frame. With a Dynamic Amplification Factor (DAF) of 1.05, the crane achieved a safe lifting capacity of 46.84 tons. The optimal configuration included a boom length of 33.50 meters, a lifting radius of 13 meters, and a sling capacity of 182.72 tons, resulting in a maximum lift capacity of 82.3 tons. This study highlights the importance of accurate lifting radius calculations and load chart optimization to ensure productivity and operational safety. The findings offer practical recommendations for application in future large-scale infrastructure projects.